NGHIÊN CỨU HIỆU QUẢ CHỐNG PHÓNG XẠ CỦA CÁC HẠT NANO CẦU VÔ ĐỊNH HÌNH VẬN CHUYỂN CHẤT CHỐNG OXY HÓA GENISTEIN - Nguyễn, Hồng Quang; V.V, Chupin; V.I, Svet; V.Yu, Kovtun; A.N, Grebenyuk (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON THE RADIATION PROTECTIVE EFFECTIVENESS OF SPHERICAL AMORPHOUS NANOPARTICLES, CHARGED WITH ANTIOXIDANT SUBSTANCE GENISTEINThis study is devoted to the preparation of the nano drug based on antioxidant substance genistein contained in spherical amorphous nanoparticles (SANp) made up of birch bark triterpenoids mixture. The results of in vivo test show that the highest radiation protective effectiveness is observed if the drug is used an hour before radiation exposure with the dose of 150 mg/kg and the use of the drug after radiation exposure is not effective.